Charge carrier dynamics investigation of Cu2S–In2S3 heterostructures for the conversion of dinitrogen to ammonia via photo-electrocatalytic reduction. Issue 16 (19th April 2021) - Bi, Ke; Wang, Yue; Zhao, Da-Ming; Wang, Jia-Zhi; Bao, Di; Shi, Miao-Miao
Abstract : Firstly, self-established photo-CELIV devices is used to performance quantitatively in operando . Secondly, we developed a catalyst for an efficient PEC-NRR possessing sufficient carriers that a reasonable recombination lifetime in the PEC process. Abstract : Photoelectrochemical (PEC) N2 fixation in aqueous solutions under ambient conditions can produce ammonia and migration of hydrogen. However, the process is limited by photocathodes with poor conversion efficiency and low production rates. Therefore, the rational design of catalyst structures is required to improve the performance and photoelectric utilization efficiency. In addition, the micro-charge carrier concentration, lifetime, and mobility cannot be quantitatively analyzed. As a result, we cannot reasonably speculate on the interaction law of microscopic carriers and macroscopic properties. Here, we successfully developed a Cu2 S–In2 S3 heterostructure catalyst for an efficient photo-electrocatalytic nitrogen reduction reaction (PEC-NRR) possessing sufficient carriers to enable higher carrier mobility and a reasonable recombination lifetime in the PEC process. The micro parameters are first quantified through a self-established photo-charge extraction by linearly increasing voltage (photo-CELIV) device and used to analyze the relationship between micro parameters and macro performance; this is of great significance for the PEC-NRR. In addition, the rare earth fluoride BaGdF5 : 30%Yb 3+, 5%Er 3+ (UCNP) material with an up-conversion effect was applied as an auxiliary light absorber to further broaden the range of sunlight absorption and reduce the ammonia reaction's energy consumption. These steps enable the Cu2 S–In2 S3 heterostructure catalyst to achieve a NH3 production rate of 23.6721 μg h −1 cm −2 and a higher faradaic efficiency (33.25% at −0.6 V versus the reversible hydrogen electrode) in aqueous solutions under ambient conditions. This special double-electrode structure provides new insights into the design of photoelectric catalytic electrodes.